2011
DOI: 10.4161/self.2.1.15087
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies: Focus on anti-DNA antibodies

Abstract: Ever since the days of Ehrlich and the birth of humoral immunity, self-reactivity or 'horror autotoxicus' as referred to by Paul Ehrlich, has been of great concern. For instance, in patients with the autoimmune disease systemic lupus erythematosus (SLE), anti-nuclear and anti-DNA antibodies have been recognized for many years. Despite this, the exact mechanism as to how the immune system fails to protect the individual and allows these autoantibodies to develop in this and other systemic autoimmune diseases re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…Relevant to these observations, telomere length measurements 21 have shown that proliferation of leukemic cells with unmutated IGHV is more intense compared to that of cells with mutated IGHV. Furthermore, it is worth men-tioning that longer VH CDR3 are a frequent feature of auto-and multi-reactive cells, 40,41 which is also in line with the reactivity profile of IGHV-unmutated CLL clones. This indicates that antigen drive may underline clonal drift leading to selection for more aggressive clones with distinctive molecular features.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 54%
See 1 more Smart Citation
“…Relevant to these observations, telomere length measurements 21 have shown that proliferation of leukemic cells with unmutated IGHV is more intense compared to that of cells with mutated IGHV. Furthermore, it is worth men-tioning that longer VH CDR3 are a frequent feature of auto-and multi-reactive cells, 40,41 which is also in line with the reactivity profile of IGHV-unmutated CLL clones. This indicates that antigen drive may underline clonal drift leading to selection for more aggressive clones with distinctive molecular features.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 54%
“…Multiple IGH rearrangements in CLL haematologica | 2014; 99(2) 337 tioning that longer VH CDR3 are a frequent feature of auto-and multi-reactive cells, 40,41 which is also in line with the reactivity profile of IGHV-unmutated CLL clones. This indicates that antigen drive may underline clonal drift leading to selection for more aggressive clones with distinctive molecular features.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 73%
“…We found that the antibodies predominantly recognized nuclear antigens staining with a homogeneous, speckled, and diffuse grainy pattern (31). This pattern is typically found with antibodies from patients with autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis (RA), indicating that the antibodies may be specific for DNA (3).…”
Section: Expansion Of the Igm Memory B Cell Subset In Chronic Hcvmentioning
confidence: 96%
“…Even though this in itself is not sufficient to tip the balance to overt autoimmunity, it could potentially result in the production of pathogenic autoantibodies. In current models of B-cell development, some degree of autoreactivity displayed by the pre-BCR appears to be critical for downstream signalling events at the pre-B-cell stage [24][25][26][27]51 . This is provided by the l5-tail that interacts with molecules on stromal cells and with neighbouring mH chains 24,26,52,53 .…”
Section: Discussionmentioning
confidence: 99%